PLIOCENE BRACHIOPODS FROM RHODES ISLAND (CAPE VAGIA SECTION) - Koskeridou, E. (Bulletin of the Geological Society of Greece, 2007)
Six brachiopod species (5 terebratulids and 1 craniid) from the upper Pliocene sandy and calcareous deposits of the Cape Vagia (Rhodes Island) are described: Gryphus sp., Terebratulina refusa, Megerlia truncata, Megerlia truncata var. monstruosa, Argyrotheca cordata, Megathiris detruncata and Novocrania anomala. This is the first record of Megerlia truncata var. monstruosa from the Pliocene of Greece and of Megerlia truncata from the Pliocene of Rhodes. Megathiris detruncata, Terebratulina retusa and Argyrotheca cordata are described for the first time from the Pliocene of Rhodes. This brachiopod association displays close affinity with those from the Mediterranean province, where assemblages of similar composition are associated with shallow-water, high energy environments. However, the association of Gryphus sp., Terebratulina retusa and Novocrania anomala corresponds to deeper water moderate environments.